Supervision and Control over the Activities of Public Benefit Organizations in the Aspect of Centralization - Bentkowska-Furman, Izabela Maria (Review of European and Comparative Law, 2021)
The main aim of this article is to look at supervision and control of public benefit organizations in Poland regarding to civil society organizations in Europe and the national supervisory systems relevant to these organizations. Also considered is the legal system in the UE, which provides recommendations for NGOs operating in its Member States. This text focuses on changes in the supervision and control over the activities of public benefit organizations in the aspect of centralization in Poland, resulting from the powers of new government administration bodies, including in particular the entitlements of the Head of the Public Benefit Committee. The aim of the research is to present and analyse the current legal solutions in the field of supervision and control over public benefit organizations in Poland and to compare the legal status with the situation before the fundamental amendment to the Act on Public Benefit and Volunteer Work.